The Effects of Irrigation and Nitrogen Application on the Water and Nitrogen Utilization Characteristics of Drip-Irrigated Winter Wheat in the North China Plain - Jingtao Qin; Xichao Fan; Xiaosen Wang; Mingliang Jiang; Mouchao Lv (Agronomy)
Reducing irrigation and nitrogen fertilizer application while maintaining crop yields is crucial for sustainable agriculture in the North China Plain. To investigate the effects of irrigation and nitrogen application on above-ground nitrogen accumulation (ANA), yield, water consumption, and the water and nitrogen use efficiency of drip-irrigated winter wheat, a three-season field experiment was conducted with four levels of nitrogen fertilizer application (250, 167, 83, and 0 kg hm−2, referred to as N3, N2, N1, and N0, respectively) and three levels of irrigation (80, 60, and 40 mm per irrigation event, referred to as W3, W1, and W1, respectively). Additionally, a control treatment (CK) was set up with almost no irrigation (only 10 mm of fertilizer water for topdressing was applied) at the N3 application level. The results indicated that over the three seasons, the average yield of irrigation treatments was 35.3% higher than that of the CK treatment under the N3 condition. Both irrigation and nitrogen application improved wheat yield and ANA; however, when irrigation exceeded W2 or nitrogen application exceeded N2, their positive effects were negligible. Due to the seasonal depletion of soil nitrogen by low-nitrogen treatments (N1 and N0), along with their other negative effects on soil health, the yields and ANA of N1 and N0 treatments gradually declined over seasons. Increased irrigation promoted evapotranspiration (ET), and when nitrogen application did not exceed N2, higher nitrogen levels also enhanced ET and soil water consumption within ET. Moderately reducing irrigation can enhance water use efficiency (WUE); however, extreme water scarcity can also decrease WUE. Compared to higher irrigation and nitrogen application treatments, the W2N2 treatment showed no significant decrease in either yield or WUE, along with an increase in NPE. Moreover, the NPFP of the N2 treatment was higher than that of the N3 treatment. Consequently, the W2N2 treatment is recommend as the optimal irrigation and nitrogen management strategy under the experimental conditions.